Study of algal flora of Navapur, District Nandurbar,Maharashtra, India. - G, Jaiswal A; G, Gavit U; R, Pathak R (International Multidisciplinary Research Journal, 2013)
The river Rangawali from Navapur of Nandurbar district ( the district Nandurbar formerly known as west Khandesh lies in upper Tapi basin in the North-West corner of Maharashtra) was selected for taxonomical enumeration of algae. Algal samples were collected from five stations of Rangawali river for a period of one year (October 2006- September 2007). In this communication chlorophyceae is studied taxonomically. 27 species belonging to 10 genera were recorded. Genus Scenedesmus was observed dominant. This is first report from this rural area of Khandesh of Maharashtra.